PENGARUH DEWAN KOMISARIS BERPENGALAMAN MILITER DAN BUDAYA ORGANISASI TERHADAP TINGKAT SUKU BUNGA (STUDI KASUS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2022) - Verayani, Renita; Rizki, Marsi Fella (AKUNTANSI DEWANTARA, 2024)
This study aims to prove the influence of military-experienced boards through the presence of military-experienced commissioners of banking companies. Then, this study also proves whether companies that use organizational culture in their financial performance can affect the interest rates set by the company. We applied purposive sampling method with various criteria in selecting the sample for this study. A total of 46 banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022 were taken as samples, and the analysis was conducted using the panel data linear regression method as well as the Random Effect Model (REM) method through the Eviews 12 application to test the hypothesis. Simultaneously, this study concludes that the board of commissioners with military experience and organizational culture simultaneously have a significant effect on interest rates of banking companies on the Indonesia Stock Exchange (IDX). However, partially this study concluded that the presence of a military-experienced board of commissioners has no influence on banking interest rates. Some organizational culture measurements such as market culture and adhocrachy culture also have no effect on banking interest rates, while other organizational culture measurements, namely clan culture and hierarchy culture have an influence on banking interest rates.